PENGARUH ECONOMIC ORDER QUANTITY DAN REORDER POINT TERHADAP TINGKAT PENJUALAN DAN KEUNTUNGAN PADA UMKM KOTA JAMBI - Hassandi, Irfan; Yosi Fadillah; Felix Filbert The; Kevin Hansiangpril (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2024)
This study aims to determine the level of sales and profits of Micro, Small, and Medium Enterprises (MSMEs) in the City of Jambi, using the Economic Order Quantity and Reorder Point methods, which will impact the operational performance of the business. The Approach that used in this research is a quantitative approach by collecting data through questionnaires. The sample size consists of 51 residents of the City of Jambi who own MSMEs and is analyzed using the SPSS application. The results of this study indicate that: (1) The Economic Order Quantity method has an influence on the level of sales and profits but is less significant. (2) The Reorder Point method has an influence on the level of sales and profits. (3) The Economic Order Quantity and Reorder Point methods have an influence on the level of sales and profits. Based on the data obtained from this research, it can be concluded that the Economic Order Quantity and Reorder Point methods can increase the level of sales and profits in MSMEs in the City of Jambi.